From Whistle to Algorithm: Human AI Collaboration in Coaching Practice in Zimbabwe (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Background: Artificial Intelligence (AI) Technologies Are Increasingly Integrated Into Sport Through Performance Analytics Platforms That Provide Detailed Insights Into Athlete Workload, Physiological Responses, And Tactical Efficiency. While These Systems Offer Unprecedented Precision, They Cannot Replicate The Human Elements Of Coaching Such As Judgment, Motivation, And Contextual Understanding. Objective: This Study Investigates How AI‑Driven Performance Analytics Can Support Coaches In Tailoring Training Programs, While Emphasizing The Irreplaceable Role Of Human Expertise In Interpreting Data And Fostering Athlete Development. Methods: A Mixed‑Methods Conceptual Analysis Was Conducted Using Survey And Interview Data From 55 Participants (20 Coaches, 30 Athletes, And 5 Sport Scientists) Drawn From Both Elite And Developmental Sport Contexts. AI Applications Including Predictive Workload Modelling, Injury Risk Profiling, And Tactical Pattern Recognition Were Examined Alongside Qualitative Accounts Of Coach-Athlete Interactions To Highlight The Interplay Between Algorithmic Insights And Human Decision Making. Results: Quantitative Findings Revealed Strong Confidence In AI Reliability, With 82% Of Coaches And Athletes Agreeing That Predictive Analytics Improved Training Personalization. However, 88% Of Respondents Emphasized The Indispensability Of Human Judgment In Contextualizing AI Outputs. Correlation Analysis Indicated A Moderate Positive Relationship () Between Athletes’ Trust In AI Systems And Their Perception Of Training Effectiveness. Qualitative Interviews Reinforced These Results, Showing That Athletes Valued AI‑Enabled Personalization But Relied On Coaches For Motivation, Trust, And Ethical Guidance. Analysts Highlighted The Importance Of Feedback Loops, Where Coaches Refine AI Outputs Based On Athlete Responses, Thereby Improving Predictive Accuracy. Conclusion: Human-AI Collaboration In Coaching Represents A Transformative Paradigm Where Algorithms Augment, But Do Not Replace, The Whistle. By Combining Data‑Driven Insights With Human Relational Expertise, Coaching Practice Can Evolve Toward More Personalized, Ethical, And Effective Athlete Support. Future Research Should Investigate Frameworks For Integrating AI Into Coaching Curricula And Explore Long‑Term Impacts On Athlete Performance And Well‑Being.